Contextualizing an early medieval village: An aristocratic family in South Jutland and a central Danish thing place. - Hartvig, Anders; Poulsen, Bjørn (Danish Journal of Archaeology, 2022)
The remains of a 12th to 14th century village, Petersborg, were recently excavated at the foot of Urnehoved Bank in Southern Jutland near the famous regional Urnehoved Thing, known from the 12th century onwards. It is suggested that a large farm in the village was inhabited by a bailiff, and that the settlement was owned by an aristocratic family named Urne. One of the members of this family is documented by an inscription on a tombstone in the church of Bjolderup, 5 km from the site. The family and its surname can be followed for centuries, and a high medieval seal matrix with their arms, found in St Clemens Church in the town of Schleswig, indicates that they were close to royal power. Written sources show that they had land in mid- and west-Schleswig. We point to a number of high-medieval settlements with the suffix ‘bøl’ in the parishes of Uge and Bjolderup near the site and suggest that the Urne family founded these clearance villages. In conclusion, we argue that Petersborg, the Urne family and the Urnehoved Thing should be seen together, thus contributing to our understanding of aristocratic elite groups in the early and high Middle Ages.